A cross sectional study of the knowledge, attitude and practice of asha workers in implementation of Janani Suraksha Yojana in Tadikonda Mandal, Guntur, Andhra Pradesh, India - Kumar Valiveti, Pavan Datta Syam; Vinjam, Brahma Naidu; Bandarupalli, Tharun; Rachamadugu, Nageswara Rao (International Journal of Research in Medical Sciences, 2017)
Background: Janani Suraksha Yojana (JSY) was evolved to reduce the maternal and neonatal mortality in India which is being implemented in Andhra Pradesh state also through ASHA workers by promoting 100% institutional deliveries to poor pregnant women. Study was undertaken to evaluate the knowledge, attitude and practices of ASHA workers in delivering the JSY services. Methods: A cross sectional community based observational study conducted in the field practice area i.e. Tadikonada Mandal of Community Medicine Department, Guntur Medical College, Guntur, Andhra Pradesh. Study sample was 50% of Tadikonda Mandal ASHA workers for 3 months (December 2012 to February 2013) with pre designed pilot tested semi structured questionnaire, Microsoft Excel. Results: Study revealed that there was 90 % of institutional deliveries, Infant Mortality Rate (IMR) was reduced to 20 per 1000 live births and Maternal Mortality Rate(MMR) was also reduced to 190 per 1,00,000 live births. Conclusions: Based on the results found in our study we came to a conclusion that in implementing the JSY services the ASHA workers are found as a back bone to reduce the IMR, MMR by promoting institutional deliveries.